Identification of Leishmania species by high-resolution DNA dissociation in cases of American cutaneous leishmaniasis, - John Verrinder Veasey; Ricardo Andrade Zampieri; Rute Facchini Lellis; Thaís Helena Proença de Freitas; Lucile Maria Floeter Winter
Abstract Background American cutaneous leishmaniasis is an infectious dermatosis caused by protozoa of the genus Leishmania, which comprises a broad spectrum of clinical manifestations depending on the parasite species involved in the infections and the immunogenetic response of the host. The use of techniques for amplification of the parasites DNA based on polymerase chain reaction polymerase chain reaction and the recent application of combined techniques, such as high-resolution DNA dissociation, have been described as a viable alternative for the detection and identification of Leishmania spp. in biological samples. Objectives To identify the Leishmania species using the polymerase chain reaction high-resolution DNA dissociation technique in skin biopsies of hospital-treated patients, and compare with results obtained by other molecular identification techniques. Methods A retrospective study assessing patients with suspected American cutaneous leishmaniasis seen at a hospital in São Paulo/Brazil was conducted. The paraffin blocks of 22 patients were analyzed by polymerase chain reaction high-resolution DNA dissociation to confirm the diagnosis and identify the species. Results Of the 22 patients with suspected American cutaneous leishmaniasis, the parasite was identified in 14, comprising five cases (35.6%) of infection by L. amazonensis, four (28.5%) by L. braziliensis, two (14.4%) by L. amazonensis + L. infantum chagasi, two (14.4%) by L. guyanensis, and one (7.1%) by Leishmania infantum chagasi. In one of the samples, in which the presence of amastigotes was confirmed on histopathological examination, the polymerase chain reaction high-resolution DNA dissociation technique failed to detect the DNA of the parasite. Study limitations The retrospective nature of the study and small number of patients. Conclusions The method detected and identified Leishmania species in paraffin-embedded skin biopsies with a sensitivity of 96.4% and could be routinely used in the public health system.